2022
DOI: 10.3390/biom12111647
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Anti-Multiple Myeloma Effects: Flavonoid, Non-Flavonoid Polyphenols, and Bortezomib

Abstract: Multiple myeloma (MM) is a clonal plasma cell tumor originating from a post-mitotic lymphoid B-cell lineage. Bortezomib(BTZ), a first-generation protease inhibitor, has increased overall survival, progression-free survival, and remission rates in patients with MM since its clinical approval in 2003. However, the use of BTZ is challenged by the malignant features of MM and drug resistance. Polyphenols, classified into flavonoid and non-flavonoid polyphenols, have potential health-promoting activities, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…However, drug efficacy is challenged by acquired drug resistance in MM. 29,39 Treatment with metformin or chidamide has been reported to sensitize MM cells to bortezomib or lenalidomide. 17,30,40 Induction of cell cycle arrest and programmed cell death such as apoptosis and autophagy is a promising strategy for anticancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, drug efficacy is challenged by acquired drug resistance in MM. 29,39 Treatment with metformin or chidamide has been reported to sensitize MM cells to bortezomib or lenalidomide. 17,30,40 Induction of cell cycle arrest and programmed cell death such as apoptosis and autophagy is a promising strategy for anticancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of an immunomodulatory drug such as lenalidomide and proteasome inhibitor such as bortezomib is usually recommended for MM patients. However, drug efficacy is challenged by acquired drug resistance in MM 29,39 . Treatment with metformin or chidamide has been reported to sensitize MM cells to bortezomib or lenalidomide 17,30,40 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the compound in combination with a first-generation protease inhibitor, Bortezomib (BTZ), in a clonal plasma cell tumor, multiple myeloma (MM) regulated by signaling cascades linked with tumor growth, medication resistance, and apoptosis. 60 Furthermore, it was investigated that wogonin potentiates TRAIL-induced growth inhibition and tumor cell death in A549 cancerous cells, as shown by the TUNEL assay. 61 In addition, it was also demonstrated that wogonin therapy reinstates the TRAIL-mediated apoptosis in the presence of ROS by upregulating p53 and PUMA in TRAIL-resistant cancer cells.…”
Section: Synergistic Effects Of Wogoninmentioning
confidence: 99%
“…Treatment with bortezomib enhances the bone marrow microenvironment by stimulating the development of osteoblasts and decreasing the activity of osteoclasts that depend on the receptor activator of NF-κB (RANKL). This effect is achieved through the activation of NF-κB, p38, and AP-1 pathways, and is influenced by the dosage of bortezomib [ 100 ]. The Phase I clinical trial study (NCT00858234) revealed that the most predominant adverse events were thrombocytopenia, leukopenia, neutropenia, diarrhea, nausea, decreased appetite, and vomiting [ 101 ].…”
Section: Introductionmentioning
confidence: 99%